Community-based rehabilitation service in Chengdu, Southwest China: a cross-sectional general survey - Siliang Chen; Yi Lei; Hua Dai; Jia Wu; Ziyu Yang; Xiaoyang Liao (BMC, 2020)
Abstract Background World Health Organization initiated community-based rehabilitation (CBR) in 1978, and by now, it has been an essential process of medical services worldwide. China had strengthened primary health care on building more than 35,000 community health centers (CHCs) in cities, and more than 34,000 township health centers (THCs) in the rural area. Nevertheless, it remains unclear that if these primary health centers could provide optional rehabilitation services for disabilities. And this study aims at evaluating the supply capacity of rehabilitation service in primary health centers of Chengdu, a regional center city of southwest China. Method We conducted a general investigation of primary health centers in Chengdu, a city located in southwest China with more than 15 million population. Our investigation covered all of Chengdu's 390 primary health centers from October to November 2016. We researched these primary health centers on basic rehabilitation services, diseases, and rehabilitation equipment quantity and quality, and traditional Chinese medicine (TCM) physiotherapy. Result Rehabilitation therapy is available in 88.9% (337 of 379) of all primary health centers. Meanwhile, CHCs slightly surpass THCs with an available rate of 92.2% (106 of 115) and 87.5% (231 of 264), respectively. Traditional Chinese Medicine (TCM) physiotherapy is available in 97.1% (368 of 379) of all primary health centers, 97.3% (112 of 115) of CHCs and 97.0% (256 of 264) of THCs. Quantitative analysis showed that substantial factors which could make an impact on the number of patients per year contain: categories of rehabilitation disease (P < 0.001, 95% confidence interval (CI) [− 1.571, − 0.702]),number of rehabilitation bed (P < 0.001, 95%CI [− 1.249, − 0.290]). Conclusion CBR and TCM physiotherapy has become accessible for disabilities in most basic health centers of Chengdu City, whereas, available rate of CBR in THCs is lesser than in CHCs, which suggests an imbalance in primary health service development between rural and urban area. Categories of rehabilitation diseases, and the number of rehabilitation beds constitute co-factors that make an impact on the CBR capacity of basic health centers.